A method for preparing ultra-low particle size activated carbon
By adding resorcinol, naphthol and sodium lignin sulfonate in the preparation process of spherical activated carbon, the problem of difficulty in preparing ultra-fine particle size activated carbon is solved, and the particle size and pore structure of activated carbon is optimized, meeting the needs of catalysts and fine chemical products.
Patent Information
- Application Number
- CN202411171904.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-08-26
AI Technical Summary
Traditional spherical activated carbon preparation methods are difficult to meet the ultra-fine particle size requirements and cannot meet the needs of certain catalyst preparation and fine chemical product production.
By adding resorcinol, naphthol and sodium lignin sulfonate, the particle size and pore structure of the resin activated carbon balls are synergistically improved, cross-linking reactions and pore formation are promoted, and uniform and fine activated carbon balls are formed.
It has achieved the acquisition of activated carbon with ultrafine particle size and developed pore structure, meeting the needs of catalyst preparation and fine chemical product production.
Smart Images

Figure BDA0005009527570000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of activated carbon preparation, and particularly relates to a method for preparing ultra-low particle size activated carbon. Background Art
[0002] Spherical activated carbon is favored for its extremely low fluid resistance in fixed bed reactors, which makes it an ideal adsorbent in the field of chemical protection, as well as an important application material in the fields of catalyst carriers and biomedicine. Due to its unique spherical structure, it can effectively improve reaction efficiency and material recycling rate, so it plays an indispensable role in many fields.
[0003] However, the traditional method of preparing spherical activated carbon mainly involves a series of complex physical and chemical processes such as solidification, carbonization and activation. Although spherical activated carbon can be obtained, its particle size distribution is often large and cannot meet the occasions with strict requirements on particle size. This leads to the fact that in the fields that require ultra-fine spherical activated carbon, such as the preparation of some special catalysts or the production of fine chemical products, traditional spherical activated carbon is difficult to meet the needs. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing ultra-low particle size activated carbon to obtain activated carbon with ultra-fine particle size.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing ultra-low particle size activated carbon comprises the following steps:
[0007] S1. Mix deionized water, anhydrous ethanol and aqueous ammonia, and stir for 10-15 minutes to obtain material A;
[0008] S2, mix resorcinol, naphthol, sodium lignin sulfonate, deionized water and anhydrous ethanol, and stir for 20-30 minutes to obtain material B;
[0009] S3. In a nitrogen atmosphere, mix the material A, material B and formaldehyde, stir for 8-10 hours, add melamine and acetic acid, stir for 20-30 minutes, reflux at 90-110° C. and stir for 4-6 hours, cool, centrifuge, wash and dry the solid phase to obtain material C;
[0010] S4, taking the material C, urea, and isopropanol, mixing, ultrasonically dispersing for 20-30 min, adding citric acid, reflux stirring at 140-160 ° C for 4-6 h, cooling, centrifuging, taking the solid phase and vacuum drying at 80 ° C for 6-8 h to obtain material D;
[0011] S5. Take the material D and place it in a tube furnace for carbonization treatment, cool it, immerse it in a potassium hydroxide solution, ultrasonically disperse it for 20-30 minutes, place it in a tube furnace for activation treatment, cool it, and then immerse it in a hydrochloric acid solution for 10-12 hours, filter it, take the solid phase, wash it to neutrality, and vacuum dry it at 90° C. for 8-10 hours to obtain the ultra-low particle size activated carbon.
[0012] As a preferred technical solution of the present invention, in step S1, the volume ratio of deionized water, anhydrous ethanol and ammonia water is 50-60:20-30:4-6.
[0013] As a preferred technical solution of the present invention, the concentration of the ammonia water is 0.1687 mol / L.
[0014] As a preferred technical solution of the present invention, in step S2, the dosage ratio of resorcinol, naphthol, sodium lignin sulfonate, deionized water and anhydrous ethanol is 0.22-0.24g: 0.26-0.28g: 0.2-0.3g: 10mL: 80-100mL.
[0015] As a preferred technical solution of the present invention, in step S3, the dosage ratio of material A, material B, formaldehyde, melamine and acetic acid is 40-60 mL: 50-54 mL: 10-12 mL: 2-3 g: 1-2 mL.
[0016] As a preferred technical solution of the present invention, in step S4, the dosage ratio of material C, urea, isopropanol and citric acid is 0.3-0.4g: 0.15-0.25g: 60-80mL: 0.4-0.6g.
[0017] As a preferred technical solution of the present invention, in step S5, the dosage ratio of the material D, potassium hydroxide solution and hydrochloric acid solution is 2-3g:10-12mL:20-30mL.
[0018] As a preferred technical solution of the present invention, the carbonization refers to keeping the temperature at 650-750° C. for 1-2 hours.
[0019] As a preferred technical solution of the present invention, the activation refers to keeping the temperature at 800° C. for 1-1.5 hours.
[0020] As a preferred technical solution of the present invention, the concentration of the potassium hydroxide solution is 1 mol / L; the concentration of the hydrochloric acid solution is 0.1 mol / L.
[0021] Beneficial effects of the present invention:
[0022] The method for preparing ultra-low particle size activated carbon disclosed in the present invention improves the particle size and pore structure of resin activated carbon balls by adding resorcinol, naphthol and sodium lignin sulfonate, wherein resorcinol and naphthol act as promoters in the polymerization process of the resin to accelerate the cross-linking reaction of the resin, form a denser network structure, and help to form a finer particle size and a more developed pore structure; sodium lignin sulfonate improves the rheological properties of the resin, promotes the formation of pores, reduces the uncross-linked phenolic chain segments in the resin activated carbon balls, thereby reducing the formation of large particle size carbon balls; and at the same time, the template effect of sodium lignin sulfonate helps to form uniform and fine activated carbon balls. DETAILED DESCRIPTION
[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0024] Example 1
[0025] A method for preparing ultra-low particle size activated carbon comprises the following steps:
[0026] S1. Mix deionized water, anhydrous ethanol and ammonia water and stir for 10 minutes to obtain material A; the volume ratio of the deionized water, anhydrous ethanol and ammonia water is 50:20:4; the concentration of the ammonia water is 0.1687 mol / L;
[0027] S2, resorcinol, naphthol, sodium lignin sulfonate, deionized water, and anhydrous ethanol were mixed and stirred for 20 minutes to obtain material B; the amount ratio of resorcinol, naphthol, sodium lignin sulfonate, deionized water, and anhydrous ethanol was 0.22g:0.26g:0.2g:10mL:80mL;
[0028] S3. In a nitrogen atmosphere, take the material A, material B, and formaldehyde, mix them, stir for 8 hours, add melamine and acetic acid, stir for 20 minutes, reflux and stir at 90°C for 4 hours, cool, centrifuge, wash and dry the solid phase to obtain material C; the dosage ratio of material A, material B, formaldehyde, melamine and acetic acid is 40mL:50mL:10mL:2g:1mL;
[0029] S4, take the material C, urea, isopropanol, mix, ultrasonically disperse for 20 minutes, add citric acid, reflux and stir at 140 ° C for 4 hours, cool, centrifuge, take the solid phase and vacuum dry at 80 ° C for 6 hours to obtain material D; the dosage ratio of the material C, urea, isopropanol, and citric acid is 0.3g:0.15g:60mL:0.4g;
[0030] S5. Take the material D and place it in a tube furnace for carbonization treatment, cool it, immerse it in a potassium hydroxide solution, ultrasonically disperse it for 20 minutes, place it in a tube furnace for activation treatment, cool it, and then immerse it in a hydrochloric acid solution for 10 hours, filter it, take the solid phase and wash it to neutrality, and vacuum dry it at 90°C for 8 hours to obtain the ultra-low particle size activated carbon; the dosage ratio of the material D, potassium hydroxide solution, and hydrochloric acid solution is 2g:10mL:20mL; the concentration of the potassium hydroxide solution is 1mol / L; the concentration of the hydrochloric acid solution is 0.1mol / L; the carbonization refers to keeping warm at 650°C for 1 hour; the activation refers to keeping warm at 800°C for 1 hour.
[0031] Example 2
[0032] A method for preparing ultra-low particle size activated carbon comprises the following steps:
[0033] S1. Mix deionized water, anhydrous ethanol and ammonia water, stir for 12 minutes, and obtain material A; the volume ratio of deionized water, anhydrous ethanol and ammonia water is 55:25:5; the concentration of ammonia water is 0.1687 mol / L;
[0034] S2, resorcinol, naphthol, sodium lignin sulfonate, deionized water, and anhydrous ethanol were mixed and stirred for 25 minutes to obtain material B; the amount ratio of resorcinol, naphthol, sodium lignin sulfonate, deionized water, and anhydrous ethanol was 0.23g:0.27g:0.25g:10mL:90mL;
[0035] S3. In a nitrogen atmosphere, take the material A, material B, and formaldehyde, mix them, stir for 9 hours, add melamine and acetic acid, stir for 25 minutes, reflux and stir at 100°C for 5 hours, cool, centrifuge, wash and dry the solid phase to obtain material C; the dosage ratio of the material A, material B, formaldehyde, melamine and acetic acid is 50mL:52mL:11mL:2.5g:1.5mL;
[0036] S4, take the material C, urea, isopropanol, mix, ultrasonically disperse for 25 minutes, add citric acid, reflux and stir at 150 ° C for 5 hours, cool, centrifuge, take the solid phase and vacuum dry at 80 ° C for 7 hours to obtain material D; the dosage ratio of the material C, urea, isopropanol and citric acid is 0.35g:0.2g:70mL:0.5g;
[0037] S5. Take the material D and place it in a tube furnace for carbonization treatment, cool it, immerse it in a potassium hydroxide solution, ultrasonically disperse it for 25 minutes, place it in a tube furnace for activation treatment, cool it, and then immerse it in a hydrochloric acid solution for 11 hours, filter it, take the solid phase and wash it to neutrality, and vacuum dry it at 90°C for 9 hours to obtain the ultra-low particle size activated carbon; the dosage ratio of the material D, potassium hydroxide solution, and hydrochloric acid solution is 2.5g:11mL:25mL; the concentration of the potassium hydroxide solution is 1mol / L; the concentration of the hydrochloric acid solution is 0.1mol / L; the carbonization refers to keeping warm at 700°C for 1.5 hours; the activation refers to keeping warm at 800°C for 1.2 hours.
[0038] Example 3
[0039] A method for preparing ultra-low particle size activated carbon comprises the following steps:
[0040] S1. Mix deionized water, anhydrous ethanol and ammonia water and stir for 15 minutes to obtain material A; the volume ratio of deionized water, anhydrous ethanol and ammonia water is 60:30:6; the concentration of ammonia water is 0.1687 mol / L;
[0041] S2, resorcinol, naphthol, sodium lignin sulfonate, deionized water, and anhydrous ethanol were mixed and stirred for 30 minutes to obtain material B; the dosage ratio of resorcinol, naphthol, sodium lignin sulfonate, deionized water, and anhydrous ethanol was 0.24g:0.28g:0.3g:10mL:100mL;
[0042] S3. In a nitrogen atmosphere, take the material A, material B, and formaldehyde, mix them, stir for 10 hours, add melamine and acetic acid, stir for 30 minutes, reflux and stir at 110° C. for 6 hours, cool, centrifuge, wash and dry the solid phase to obtain material C; the dosage ratio of material A, material B, formaldehyde, melamine and acetic acid is 60 mL: 54 mL: 12 mL: 3 g: 2 mL;
[0043] S4, take the material C, urea, isopropanol, mix, ultrasonically disperse for 30 minutes, add citric acid, reflux and stir at 160 ° C for 6 hours, cool, centrifuge, take the solid phase and vacuum dry at 80 ° C for 8 hours to obtain material D; the dosage ratio of the material C, urea, isopropanol, and citric acid is 0.4g:0.25g:80mL:0.6g;
[0044] S5. Take the material D and place it in a tube furnace for carbonization treatment, cool it, immerse it in a potassium hydroxide solution, ultrasonically disperse it for 30 minutes, place it in a tube furnace for activation treatment, cool it, and then immerse it in a hydrochloric acid solution for 12 hours, filter it, take the solid phase and wash it to neutrality, and vacuum dry it at 90°C for 10 hours to obtain the ultra-low particle size activated carbon; the dosage ratio of the material D, potassium hydroxide solution, and hydrochloric acid solution is 3g:12mL:30mL; the concentration of the potassium hydroxide solution is 1mol / L; the concentration of the hydrochloric acid solution is 0.1mol / L; the carbonization refers to keeping warm at 750°C for 2 hours; the activation refers to keeping warm at 800°C for 1.5 hours.
[0045] Comparative Example 1
[0046] A method for preparing ultra-low particle size activated carbon comprises the following steps:
[0047] S1. Mix deionized water, anhydrous ethanol and ammonia water, stir for 12 minutes, and obtain material A; the volume ratio of deionized water, anhydrous ethanol and ammonia water is 55:25:5; the concentration of ammonia water is 0.1687 mol / L;
[0048] S2, taking naphthol, sodium lignin sulfonate, deionized water, and anhydrous ethanol, mixing and stirring for 25 minutes to obtain material B; the dosage ratio of naphthol, sodium lignin sulfonate, deionized water, and anhydrous ethanol is 0.5g:0.25g:10mL:90mL;
[0049] S3. In a nitrogen atmosphere, take the material A, material B, and formaldehyde, mix them, stir for 9 hours, add melamine and acetic acid, stir for 25 minutes, reflux and stir at 100°C for 5 hours, cool, centrifuge, wash and dry the solid phase to obtain material C; the dosage ratio of the material A, material B, formaldehyde, melamine and acetic acid is 50mL:52mL:11mL:2.5g:1.5mL;
[0050] S4, take the material C, urea, isopropanol, mix, ultrasonically disperse for 25 minutes, add citric acid, reflux and stir at 150 ° C for 5 hours, cool, centrifuge, take the solid phase and vacuum dry at 80 ° C for 7 hours to obtain material D; the dosage ratio of the material C, urea, isopropanol and citric acid is 0.35g:0.2g:70mL:0.5g;
[0051] S5. Take the material D and place it in a tube furnace for carbonization treatment, cool it, immerse it in a potassium hydroxide solution, ultrasonically disperse it for 25 minutes, place it in a tube furnace for activation treatment, cool it, and then immerse it in a hydrochloric acid solution for 11 hours, filter it, take the solid phase and wash it to neutrality, and vacuum dry it at 90°C for 9 hours to obtain the ultra-low particle size activated carbon; the dosage ratio of the material D, potassium hydroxide solution, and hydrochloric acid solution is 2.5g:11mL:25mL; the concentration of the potassium hydroxide solution is 1mol / L; the concentration of the hydrochloric acid solution is 0.1mol / L; the carbonization refers to keeping warm at 700°C for 1.5 hours; the activation refers to keeping warm at 800°C for 1.2 hours.
[0052] Comparative Example 2
[0053] A method for preparing ultra-low particle size activated carbon comprises the following steps:
[0054] S1. Mix deionized water, anhydrous ethanol and ammonia water, stir for 12 minutes, and obtain material A; the volume ratio of deionized water, anhydrous ethanol and ammonia water is 55:25:5; the concentration of ammonia water is 0.1687 mol / L;
[0055] S2, resorcinol, sodium lignin sulfonate, deionized water, and anhydrous ethanol were mixed and stirred for 25 minutes to obtain material B; the amount ratio of resorcinol, sodium lignin sulfonate, deionized water, and anhydrous ethanol was 0.5g:0.25g:10mL:90mL;
[0056] S3. In a nitrogen atmosphere, take the material A, material B, and formaldehyde, mix them, stir for 9 hours, add melamine and acetic acid, stir for 25 minutes, reflux and stir at 100°C for 5 hours, cool, centrifuge, wash and dry the solid phase to obtain material C; the dosage ratio of the material A, material B, formaldehyde, melamine and acetic acid is 50mL:52mL:11mL:2.5g:1.5mL;
[0057] S4, take the material C, urea, isopropanol, mix, ultrasonically disperse for 25 minutes, add citric acid, reflux and stir at 150 ° C for 5 hours, cool, centrifuge, take the solid phase and vacuum dry at 80 ° C for 7 hours to obtain material D; the dosage ratio of the material C, urea, isopropanol and citric acid is 0.35g:0.2g:70mL:0.5g;
[0058] S5. Take the material D and place it in a tube furnace for carbonization treatment, cool it, immerse it in a potassium hydroxide solution, ultrasonically disperse it for 25 minutes, place it in a tube furnace for activation treatment, cool it, and then immerse it in a hydrochloric acid solution for 11 hours, filter it, take the solid phase and wash it to neutrality, and vacuum dry it at 90°C for 9 hours to obtain the ultra-low particle size activated carbon; the dosage ratio of the material D, potassium hydroxide solution, and hydrochloric acid solution is 2.5g:11mL:25mL; the concentration of the potassium hydroxide solution is 1mol / L; the concentration of the hydrochloric acid solution is 0.1mol / L; the carbonization refers to keeping warm at 700°C for 1.5 hours; the activation refers to keeping warm at 800°C for 1.2 hours.
[0059] Comparative Example 3
[0060] A method for preparing ultra-low particle size activated carbon comprises the following steps:
[0061] S1. Mix deionized water, anhydrous ethanol and ammonia water, stir for 12 minutes, and obtain material A; the volume ratio of deionized water, anhydrous ethanol and ammonia water is 55:25:5; the concentration of ammonia water is 0.1687 mol / L;
[0062] S2, sodium lignin sulfonate, deionized water, and anhydrous ethanol were mixed and stirred for 25 minutes to obtain material B; the amount ratio of resorcinol, naphthol, sodium lignin sulfonate, deionized water, and anhydrous ethanol was 0.75g:10mL:90mL;
[0063] S3. In a nitrogen atmosphere, take the material A, material B, and formaldehyde, mix them, stir for 9 hours, add melamine and acetic acid, stir for 25 minutes, reflux and stir at 100°C for 5 hours, cool, centrifuge, wash and dry the solid phase to obtain material C; the dosage ratio of the material A, material B, formaldehyde, melamine and acetic acid is 50mL:52mL:11mL:2.5g:1.5mL;
[0064] S4, take the material C, urea, isopropanol, mix, ultrasonically disperse for 25 minutes, add citric acid, reflux and stir at 150 ° C for 5 hours, cool, centrifuge, take the solid phase and vacuum dry at 80 ° C for 7 hours to obtain material D; the dosage ratio of the material C, urea, isopropanol and citric acid is 0.35g:0.2g:70mL:0.5g;
[0065] S5. Take the material D and place it in a tube furnace for carbonization treatment, cool it, immerse it in a potassium hydroxide solution, ultrasonically disperse it for 25 minutes, place it in a tube furnace for activation treatment, cool it, and then immerse it in a hydrochloric acid solution for 11 hours, filter it, take the solid phase and wash it to neutrality, and vacuum dry it at 90°C for 9 hours to obtain the ultra-low particle size activated carbon; the dosage ratio of the material D, potassium hydroxide solution, and hydrochloric acid solution is 2.5g:11mL:25mL; the concentration of the potassium hydroxide solution is 1mol / L; the concentration of the hydrochloric acid solution is 0.1mol / L; the carbonization refers to keeping warm at 700°C for 1.5 hours; the activation refers to keeping warm at 800°C for 1.2 hours.
[0066] Comparative Example 4
[0067] A method for preparing ultra-low particle size activated carbon comprises the following steps:
[0068] S1. Mix deionized water, anhydrous ethanol and ammonia water, stir for 12 minutes, and obtain material A; the volume ratio of deionized water, anhydrous ethanol and ammonia water is 55:25:5; the concentration of ammonia water is 0.1687 mol / L;
[0069] S2, resorcinol, naphthol, deionized water, and anhydrous ethanol were mixed and stirred for 25 minutes to obtain material B; the amount ratio of resorcinol, naphthol, deionized water, and anhydrous ethanol was 0.48g:0.27g:10mL:90mL;
[0070] S3. In a nitrogen atmosphere, take the material A, material B, and formaldehyde, mix them, stir for 9 hours, add melamine and acetic acid, stir for 25 minutes, reflux and stir at 100°C for 5 hours, cool, centrifuge, wash and dry the solid phase to obtain material C; the dosage ratio of the material A, material B, formaldehyde, melamine and acetic acid is 50mL:52mL:11mL:2.5g:1.5mL;
[0071] S4, take the material C, urea, isopropanol, mix, ultrasonically disperse for 25 minutes, add citric acid, reflux and stir at 150 ° C for 5 hours, cool, centrifuge, take the solid phase and vacuum dry at 80 ° C for 7 hours to obtain material D; the dosage ratio of the material C, urea, isopropanol and citric acid is 0.35g:0.2g:70mL:0.5g;
[0072] S5. Take the material D and place it in a tube furnace for carbonization treatment, cool it, immerse it in a potassium hydroxide solution, ultrasonically disperse it for 25 minutes, place it in a tube furnace for activation treatment, cool it, and then immerse it in a hydrochloric acid solution for 11 hours, filter it, take the solid phase and wash it to neutrality, and vacuum dry it at 90°C for 9 hours to obtain the ultra-low particle size activated carbon; the dosage ratio of the material D, potassium hydroxide solution, and hydrochloric acid solution is 2.5g:11mL:25mL; the concentration of the potassium hydroxide solution is 1mol / L; the concentration of the hydrochloric acid solution is 0.1mol / L; the carbonization refers to keeping warm at 700°C for 1.5 hours; the activation refers to keeping warm at 800°C for 1.2 hours.
[0073] Performance Testing
[0074] The activated carbons prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to comprehensive performance tests, and the test results are shown in Table 1 below.
[0075] Table 1
[0076]
[0077] As shown in Table 1, the activated carbon obtained by Examples 1-3 of the present application has a finer particle size, a more developed pore structure and an adsorption effect; this is because the present application adds resorcinol, naphthol, and sodium lignin sulfonate to synergistically improve the particle size and pore structure of the resin activated carbon ball, wherein resorcinol and naphthol act as promoters during the polymerization of the resin to accelerate the cross-linking reaction of the resin, form a more compact network structure, and contribute to the formation of a finer particle size and a more developed pore structure, and sodium lignin sulfonate improves the rheological properties of the resin, promotes the formation of pores, reduces the uncross-linked phenolic segments in the resin activated carbon ball, thereby reducing the formation of large-particle carbon balls, and at the same time, the template effect of sodium lignin sulfonate contributes to the formation of uniform and fine activated carbon balls. In addition, by doping nitrogen, sulfur, and oxygen elements, the resin activated carbon ball is more prone to defects during the carbonization process, and these defects change the grain size and arrangement of the activated carbon, forming a more delicate particle size structure.
[0078] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing ultra-low particle size activated carbon, characterized in that: The following steps are involved: S1. Mix deionized water, anhydrous ethanol and aqueous ammonia, and stir for 10-15 minutes to obtain material A; S2, mix resorcinol, naphthol, sodium lignin sulfonate, deionized water and anhydrous ethanol, and stir for 20-30 minutes to obtain material B; S3. In a nitrogen atmosphere, mix the material A, material B and formaldehyde, stir for 8-10 hours, add melamine and acetic acid, stir for 20-30 minutes, reflux at 90-110° C. and stir for 4-6 hours, cool, centrifuge, wash and dry the solid phase to obtain material C; S4, taking the material C, urea, and isopropanol, mixing, ultrasonically dispersing for 20-30 min, adding citric acid, reflux stirring at 140-160 ° C for 4-6 h, cooling, centrifuging, taking the solid phase and vacuum drying at 80 ° C for 6-8 h to obtain material D; S5, taking the material D and placing it in a tube furnace for carbonization treatment, cooling, immersing it in a potassium hydroxide solution, ultrasonically dispersing it for 20-30 minutes, placing it in a tube furnace for activation treatment, cooling, and then immersing it in a hydrochloric acid solution for 10-12 hours, filtering, washing the solid phase to neutrality, and vacuum drying it at 90° C. for 8-10 hours to obtain the ultra-low particle size activated carbon; In step S1, the volume ratio of deionized water, anhydrous ethanol and aqueous ammonia is 50-60:20-30:4-6; In step S2, the ratio of resorcinol, naphthol, sodium lignin sulfonate, deionized water and anhydrous ethanol is 0.22-0.24 g: 0.26-0.28 g: 0.2-0.3 g: 10 mL: 80-100 mL; In step S3, the dosage ratio of material A, material B, formaldehyde, melamine and acetic acid is 40-60 mL: 50-54 mL: 10-12 mL: 2-3 g: 1-2 mL; In step S4, the dosage ratio of material C, urea, isopropanol and citric acid is 0.3-0.4 g: 0.15-0.25 g: 60-80 mL: 0.4-0.6 g; In step S5, the dosage ratio of the material D, potassium hydroxide solution and hydrochloric acid solution is 2-3 g: 10-12 mL: 20-30 mL.
2. The method for preparing ultra-low particle size activated carbon according to claim 1, characterized in that: The carbonization refers to keeping the temperature at 650-750° C. for 1-2 hours.
3. The method for preparing ultra-low particle size activated carbon according to claim 1, characterized in that: The activation refers to keeping the temperature at 800° C. for 1-1.5 hours.
Citation Information
Patent Citations
Method for preparing carbon nanospheres based on mixed phenol and carbon nanospheres
CN113666360A
Method for preparing carbon nanospheres based on medium and low temperature coal tar and carbon nanospheres
CN115707651A